Development and evaluation of a 16‐channel receive‐only RF coil to improve 7T ultra‐high field body MRI with focus on the spine. Issue 2 (28th March 2019) - Rietsch, Stefan H. G.; Brunheim, Sascha; Orzada, Stephan; Voelker, Maximilian N.; Maderwald, Stefan; Bitz, Andreas K.; Gratz, Marcel; Ladd, Mark E.; Quick, Harald H.
Abstract : Purpose: A 16‐channel receive (16Rx) radiofrequency (RF) array for 7T ultra‐high field body MR imaging is presented. The coil is evaluated in conjunction with a 16‐channel transmit/receive (16TxRx) coil and additionally with a 32‐channel transmit/receive (32TxRx) remote body coil for RF transmit and serving as receive references. Methods: The 16Rx array consists of 16 octagonal overlapping loops connected to custom‐built detuning boards with preamplifiers. Performance metrics like noise correlation, g‐factors, and signal‐to‐noise ratio gain were compared between 4 different RF coil configurations. In vivo body imaging was performed in volunteers using radiofrequency shimming, time interleaved acquisition of modes (TIAMO), and 2D spatially selective excitation using parallel transmit (pTx) in the spine. Results: Lower g‐factors were obtained when using the 16Rx coil in addition to the 16TxRx array coil configuration versus the 16TxRx array alone. Distinct signal‐to‐noise ratio gain using the 16Rx coil could be demonstrated in the spine region both for a comparison with the 16TxRx coil (>50% gain) in vivo and the 32TxRx coil (>240% gain) in a phantom. The 16Rx coil was successfully applied to improve anatomical imaging in the abdomen and 2D spatially selective excitation in the spine of volunteers. Conclusion: The novel 16‐channel Rx‐array as an add‐on to multichannel TxRx RF coil configurations provides increased signal‐to‐noise ratio, lower g‐factors, and thus improves 7T ultra‐high field body MR imaging.